Fabrication And Characterization Of Tio2 - Pvp Nanofibre Using Electrospinning Method For Hydrogen Gas Sensing - Abed, Nabeel Zabar (2016)
In this project, anatase phase titanium dioxide (TiO2) nanofibers (NFs) are successfully fabricated using the homemade electrospinning (ES) method. This study aims to fabricate uniform and high quality anatase TiO2/polyvinylpyrrolidone (PVP) NFs on the glass substrate. A number of parameters were studied for the development of best form of nanofibers; the most suitable/optimised parameters for the fabrication of hydrogen gas sensor device were found at room temperature. Xray diffraction (XRD) patterns show sharp and well-defined peaks identified as anatase phase.